In vitro antimicrobial activity of a new series of 1,4-naphthoquinones - Riffel,A. (2002)
The antibacterial activity of a series of 1,4-naphthoquinones was demonstrated. Disk diffusion tests were carried out against several Gram-positive and Gram-negative bacteria. The compound 5-amino-8-hydroxy-1,4-naphthoquinone was the most effective, presenting inhibition zones measuring 20 mm against staphylococci, streptococci and bacilli at 50 µg/ml. Methicillin-resistant Staphylococcus aureus and several clinical isolates of this bacterium were also inhibited. Naphthazarin, 5-acetamido-8-hydroxy-1,4-naphthoquinone, and 2,3-diamino-1,4-naphthoquinone were the next most active compounds. The minimal inhibitory concentration of the active compounds was determined against S. aureus, ranging from 30 to 125 µg/ml. All compounds presented a minimal bactericidal concentration higher than 500 µg/ml, indicating that their effect was bacteriostatic. The EC50, defined as the drug concentration that produces 50% of maximal effect, was 8 µg/ml for 5-amino-8-hydroxy-1,4-naphthoquinone against S. aureus, S. intermedius, and S. epidermidis. These results indicate an effective in vitro activity of 5-amino-8-hydroxy-1,4-naphthoquinone and encourage further studies for its application in antibiotic therapy.